2012
DOI: 10.1109/led.2012.2191386
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fixed Charge in Tunnel-Barrier Contacts for Fermi-Level Depinning in Germanium

Abstract: Recent experiments have demonstrated a reduction of Fermi-level pinning in contacts to n-type Ge by the insertion of a thin tunnel barrier at the interface. The presence of fixed charge in these interface layers can contribute to Schottky-barrier reduction. This work theoretically studies the effect of tunnelbarrier fixed charge on the specific contact resistivity. By simulating various tunnel-barrier materials and fixed-charge densities, we estimate the magnitude of fixed charge required for this mechanism to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…In semiconductor/metal junctions, a similar effect has been reported that the contact resistance of the junctions is considerably reduced by inserting a thin-insulating layer between the semiconductor and metal layer, where the insulating layer has thickness of lower than ∼2 nm (refs 17 , 18 ). In this geometry, the electron introduced in the metal electrode must be injected to the mobile bands of the semiconductor by quantum mechanical tunnelling effect, and then this type of contact is referred to as ‘tunnel contact' or ‘tunnel-barrier contact'.…”
Section: Resultsmentioning
confidence: 62%
“…In semiconductor/metal junctions, a similar effect has been reported that the contact resistance of the junctions is considerably reduced by inserting a thin-insulating layer between the semiconductor and metal layer, where the insulating layer has thickness of lower than ∼2 nm (refs 17 , 18 ). In this geometry, the electron introduced in the metal electrode must be injected to the mobile bands of the semiconductor by quantum mechanical tunnelling effect, and then this type of contact is referred to as ‘tunnel contact' or ‘tunnel-barrier contact'.…”
Section: Resultsmentioning
confidence: 62%
“…In the presence of fixed charges, a plot of the flat-band voltage against the insulator thickness could exhibit a straight line, in which case the slope gives the density of the fixed charge residing at the insulator-semiconductor interface, or the plot could exhibit a curve, in which case the slope extrapolated to zero thickness would give the amount of interface fixed charge and the curvature indicates the density of charge residing inside the insulator. For the present discussion involving very thin interlayers, the distinction between the two types of fixed charge is unnecessary and one can simply assume an areal density of (positive) fixed charge, en f xch , to reside at the I-S interface, 330,331 from which the following zero-bias n-type SBH for the MIS stack can be derived …”
Section: B Sbh Modification With Thin Layer Of Insulating Materialsmentioning
confidence: 99%
“…The technique was also demonstrated on III-V semiconductors by Hu et al 15 The presence of fixed charges within interlayers has also been proposed to explain reduced contact resistance. 16 In separate studies, reductions in metal/interlayer/semiconductor (MIS) contact resistance have been reported on n-type and p-type 10 15 cm À3 doped Si substrates. Coss et al 17 used TaN electrodes and explained the improvement in contact resistance to p-type Si in terms of AlO x /SiO 2 dipoles.…”
mentioning
confidence: 99%